Uncertainties experienced by nursing professionals who contracted Covid-19: a priori, everyone is human - Cinthia Rafaela Amaro Gonçalves Andrade; Laís de Miranda Crispim Costa; Ingrid Martins Leite Lúcio; Janaina Ferro Pereira; Herika do Nascimento Lima; Renata Lira do Nascimento (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To analyze the uncertainties experienced by nursing professionals who contracted COVID-19. Methods: This qualitative research was conducted with 20 nursing professionals who fell ill from COVID-19. Data collection was carried out through semi-structured interviews; the data were then organized using thematic analysis and discussed in the context of Merle Mishel's Reconceptualized of Uncertainty in Illness Theory. Results: The antecedents of the disease had a strong influence on how nursing professionals who contracted COVID-19 perceived uncertainty. The media coverage of the increasing number of cases, the collapse of the healthcare system, and the high mortality rate contributed to associating the disease with fear and panic. Final Considerations: Viewing it from the perspective of the disease's antecedents, the illness of a nursing professional from COVID-19 underscores that before being professionals, they are human beings just like anyone else, undergoing adversities and facing the possibilities associated with being ill.